Migration of Very Long Period Seismicity at Aso Volcano, Japan, Associated With the 2016 Kumamoto Earthquake. Issue 15 (8th August 2019) - Hendriyana, Andri; Tsuji, Takeshi
Abstract: Earthquakes are known to precede volcanic activity, including long‐period or very long period (VLP) volcanic seismicity. However, the relationships among earthquakes, VLP seismicity, and volcanic eruptions are not well understood. Here we present the locations of VLP seismicity at Aso volcano, Japan, between January 2015 and December 2016, a period that includes the M w 7.0 Kumamoto earthquake and phreatomagmatic eruptions. By using a differential‐time backprojection method developed in this study to accurately locate VLP events, we clearly identified two distinct VLP clusters. Whereas the eastern cluster was active during eruptions, the western cluster displayed intense VLP seismicity only for a few months after the earthquake. The western cluster may be associated with opening of new fractures during the earthquake. This study explores the mechanisms that can relate earthquake to volcanic activities and provides a new approach to analyze the dynamic behaviors inside volcanoes that may yield useful information for hazard evaluation. Plain Language Summary: The relationship between earthquake and volcanic seismicity is studied by analyzing continuous seismic data recorded between January 2015 and December 2016, a period that includes the M w 7.0 Kumamoto earthquake and volcanic eruptions at Aso. This study focuses on analyzing very long period (VLP) seismic event with a period of 15 s that can be explained by pressure fluctuation within hydrothermal systems. The intense activity of long‐period event could be an indication of impending eruptions. By using our developed localization method, we revealed two clusters of VLP sources, namely, eastern and western clusters. The eastern cluster was always active during an active period of Aso volcano. However, the western cluster showed intense VLP seismicity only for a few months after the earthquake. The western cluster could be associated with opening of new cracks triggered by the Kumamoto earthquake. This study suggests a strong relationship between distant large earthquake with volcanic seismicity that could be useful for disaster mitigation. Moreover, monitoring of temporal and spatial evolution of VLP sources may be considered as a tool to study the response of volcanic activity to ground shaking from large earthquake. Key Points: Backprojection technique based on differential‐time and phase weighted stacking is used to map clusters of very long period seismicity Clusters of very long period seismicity indicate clear relationship between distant earthquake and volcanic activities The 2016 Kumamoto earthquake suddenly induced very long period seismicity at west of Aso Caldera lasting for five months